Hourly extreme rainfall projections over South Korea using convection permitting climate simulations - Ga-Yeong Seo; Seung-Ki Min; Donghyun Lee; Seok-Woo Son; Chanil Park; Dong-Hyun Cha (npj Climate and Atmospheric Science)
Abstract This study analyzes the impact of climate change on the summertime hourly extreme rainfall event (HER) over South Korea. The UKESM-forced regional climate model is utilized to simulate HER over South Korea in the historical (2001–2005) and future periods (2091–2095) under the SSP1-2.6 and SSP5-8.5 scenarios at a convection-permitting resolution (2.5 km). A significant increase in future HER intensity and frequency appears in July, with the frequency increases about two times for SSP1-2.6 and about 3.7 times for SSP5-8.5 scenarios. The month of maximum HER frequency is also projected to shift from August to July. When clustering the HERs into six representative weather patterns, SSP5-8.5 scenarios show a predominant increase in weather patterns characterized by a frontal boundary between low and high pressure in July. Our results suggest that the future sub-seasonal evolution of HER over South Korea may change with the intensification of subtropical high and the deepening of mid-level trough according to different future scenarios.